Digital Anecdote Text Module Oriented to Critical Thinking for SMA/MA/SMK Students - Kadariyah; Rozak, Abdul; Gloriani , Yusida (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to find out and fulfill the needs for teaching materials, especially anecdotal text materials in digital form and their implementation so that they can improve the critical thinking skills of SMA/MA/SMK students. The method used in this research is research and development. The results obtained are that the digital editorial text module in improving the critical thinking skills of SMA/MA/SMK students is suitable for use as teaching material. Learning resources in the form of several editorial texts from several mass media, which were analyzed, met structural, linguistic and critical thinking aspects as teaching materials developed in the form of digital modules. The development of editorial text teaching materials is adjusted to indicators of competency achievement and basic competencies that are validated by experts and practitioners to obtain a category as teaching materials that are suitable for use in SMA/MA/SMK Indramayu Regency. Based on the results of testing the module in learning, it is known that the module is effective in improving the critical thinking skills of SMA/MA/SMK students